Glass fiber composition with low dielectric loss

The glass fiber composition with optimized component ratios and raw materials addresses high dielectric loss and viscosity issues, achieving low dielectric constant, low dielectric loss, and zero bubbles, improving mechanical strength and production efficiency.

JP7621519B2Active Publication Date: 2025-01-24TAISHAN FIBERGLASS INC +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023574328
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-10
Filing Date
2022-08-10
Publication Date
2025-01-24
Estimated Expiration
2042-08-10

AI Technical Summary

Technical Problem

Existing glass fibers exhibit high dielectric loss and viscosity, particularly at high frequencies, and are challenging to produce at scale with zero bubbles.

Method used

A glass fiber composition with specific component ratios: SiO2 50-60%, B2O3 20-30%, Al2O3 8-18%, CaO 1-6%, F2 0.2-1.50%, SnO2 0.05-0.5%, Li2O 0.05-0.5%, K2O+Na2O ≤0.05%, with controlled ratios of SnO2/Li2O, F2/SnO2, and P2O5/(F2+SnO2) to achieve low dielectric constant, low dielectric loss, and low viscosity, using quartz powder, boric anhydride, alumina, wollastonite, magnesium oxide, tin oxide, fluorite, and aluminum metaphosphate as raw materials.

Benefits of technology

The composition achieves low dielectric constant and loss, low viscosity, and zero bubbles, enhancing mechanical strength and production efficiency with controlled component interactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621519000001
    Figure 0007621519000001
  • Figure 0007621519000002
    Figure 0007621519000002
  • Figure 0007621519000003
    Figure 0007621519000003
Patent Text Reader

Abstract

The present invention belongs to the technical field of glass fibers, and more particularly to a glass fiber composition with low dielectric loss. The contents of each component of the composition are SiO2: 50-60%, B2O3: 20-30%, Al2O3: 8-18%, CaO: 1-6%, F2: 0.2-1.50%, SnO2: 0.05-0.5%, Li2O: 0.05-0.5%, and K2O+Na2O≦0.05%. The present invention adds SnO2 and F2 simultaneously and controls the ratio of F2 / SnO2, thereby not only reducing the dielectric constant and dielectric loss of the glass fiber, but also reducing the viscosity of the glass fiber, so that the number of bubbles in the glass fiber becomes zero. The present invention provides a glass fiber composition with low dielectric constant, low dielectric loss, low bubbles, and low viscosity due to the interaction between each component, and excellent glass performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of glass fibers, and more particularly to glass fiber compositions having low dielectric loss. [Background technology]

[0002] With the development of 5G communication, the performance requirements for low dielectric constant materials will become more stringent. The biggest advantage of 5G is its high transmission speed, but the biggest drawback is its large penetration difference and attenuation. Glass converts part of the electrical energy in high-frequency electromagnetic fields into thermal energy, generating losses. This requires the transmission medium material to have the characteristics of low dielectric constant and small dielectric loss, which can achieve faster signal transmission, lower signal delay, and higher signal fidelity.

[0003] Chinese patent CN102503153A discloses a low dielectric constant glass fiber containing 48wt%-58wt% SiO2, 10wt%-18wt% Al2O3, 18wt%-28wt% B2O3, 0wt%-6wt% CaO, 0wt%-6wt% MgO, 0.5wt%-8wt% Y2O3, 0.2wt%-0.6wt% CeO2, 0wt%-3wt% F2, 0wt%-1wt% Na2O, K2O and Li2O, 0wt%-0.45wt% TiO2, and 0wt%-0.5wt% Fe2O3. The glass fiber has a dielectric constant of 4.1-4.5 and a dielectric loss of 6×10 at room temperature and a frequency of 1MHz. -4 ~9×10 -4 It is.

[0004] Chinese patent CN104556710A discloses a modified glass fiber and a manufacturing method thereof, the modified glass fiber contains the following components in mole percentage: SiO2 52%-58%, B2O3 16%-24%, Al2O3 13%-19%, CaO 1%-5%, MgO 4.2%-8%, F2 0.4%-2%, Li2O 0-0.5%, Fe2O3 0-0.4%, K2O 0-0.2%, Na2O 0-0.2%. The modified glass fiber has a dielectric constant of less than 4.7 and a dielectric loss factor of 10 at room temperature and a frequency of 1 MHz.-3 is less than.

[0005] Chinese patent CN103482876A discloses a low dielectric constant glass fiber for printed wiring boards, which contains the following mass percentages of components: 48%-53% SiO2, 13%-16% Al2O3, 19%-25% B2O3, 50.5%-2% P2O, 5.0%-8.5% CaO, 0.5%-8% La2O3, 0.5%-2.5% ZnO, 0.5%-2.5% TiO2, less than 1% Na2O, K2O and Li2O, less than 0.45% SO3, and less than 0.45% Fe2O3. It has a very low dielectric constant and dielectric loss, with a dielectric constant of 4.8-5.5 and a dielectric loss of 4-8×10 at room temperature and a frequency of 1 MHz. -4 It is.

[0006] The glass fiber in the above patent document has a low viscosity, but the dielectric performance was measured under the condition of 1 MHz, and the dielectric loss of glass increases as the frequency increases. For example, at room temperature and 1 MHz, the tan δ of silicate glass is 9×10 -4 At 3000MHz, it is 36×10 -4 Therefore, in the above patent, the dielectric loss is relatively low only when detected at room temperature and 1 MHz.

[0007] Chinese patent CN113135666A discloses low dielectric glass fiber containing SiO2: 50-58%, Al2O3: 10-16%, B2O3: 20-28%, MgO: 1-4%, CaO: 1-4%, Li2O: 0.05-0.5%, Na2O: 0.05-0.6%, K2O: 0.05-0.8%, TiO2: 0.2-1.5%, CeO2: 0-1%, SnO2: 0.01-1.5%, and Fe2O3: 0-0.1%. By appropriately setting the ratio of silica, alumina, and boron oxide, the glass fiber is given a low dielectric constant and dielectric loss, and the glass viscosity is appropriately adjusted. At room temperature and a frequency of 10 GHz, the glass fiber has a dielectric constant of 4.2-4.5 and a dielectric loss of 2.5×10 -3 ~4.4×10 -3 In this patent, the dielectric constant and dielectric loss are high.

[0008] Based on the above problems, there is an urgent need to develop a glass fiber composition that has low dielectric constant, low dielectric loss, low viscosity, and zero bubbles, which is suitable for scale production at high frequencies. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a glass fiber composition having a low dielectric constant, low dielectric loss, low viscosity and zero bubbles. [Means for solving the problem]

[0010] The glass fiber composition having low dielectric loss according to the present invention has a content of each component, in mass percentage, of: SiO2: 50-60%, B2O3: 20-30%, Al2O3: 8-18%, CaO: 1-6%, F2: 0.2-1.50%, SnO2: 0.05-0.5%, Li2O: 0.05-0.5%, K2O+Na2O≦0.05%.

[0011] Preferably, the glass fiber composition having low dielectric loss has a content of each component, in mass percentage, of: SiO2: 50-60%, B2O3: 20-30%, Al2O3: 8-18%, CaO: 1-6%, F2: 0.2-1.50%, P2O5: 0.05-5%, SnO2: 0.05-0.5%, Li2O: 0.05-0.5%, K2O+Na2O≦0.05%.

[0012] Preferably, the glass fiber composition having low dielectric loss has a content of each component, in mass percentage, of: SiO2: 50-60%, B2O3: 20-30%, Al2O3: 8-18%, CaO: 1-6%, F2: 0.2-1.50%, SnO2: 0.05-0.5%, Li2O: 0.05-0.5%, K2O+Na2O≦0.05%, 0 <MgO<2.0である。

[0013] Preferably, the glass fiber composition having low dielectric loss has a content of each component, in mass percentage, of: SiO2: 50-60%, B2O3: 20-30%, Al2O3: 8-18%, CaO: 1-6%, F2: 0.2-1.50%, P2O5: 0.05-5%, SnO2: 0.05-0.5%, Li2O: 0.05-0.5%, K2O+Na2O≦0.05%, 0 <MgO<2.0である。

[0014] Where: The mass percentage contents of SnO2 and Li2O satisfy the range of SnO2 / Li2O being 0.2-3. The mass percentage contents of F2 and SnO2 satisfy the range of F2 / SnO2 being 1-5. The mass percentage contents of P2O5, F2 and SnO2 satisfy the range of P2O5 / (F2+SnO2) being 2-5.

[0015] The raw materials for producing the glass fiber composition in the present invention are quartz powder, boric anhydride, alumina, wollastonite, magnesium oxide, tin oxide, fluorite, aluminum metaphosphate, and spodumene. Effect of the Invention

[0016] The beneficial effects of the present invention are as follows:

[0017] SiO2 is a silicone tetrahedral structure that forms an irregular continuous network structure. This structure has high bond strength, is tightly packed, is not easily polarized by an external electric field, and is not easily affected by losses such as conductance or relaxation. Therefore, when the SiO2 content is high, the glass dielectric constant and dielectric loss are significantly reduced, and mechanical strength is increased. However, when the content is high, the viscosity increases, making melting and smelting more difficult. For example, quartz glass has a very low dielectric loss of 0.0001, but has a high viscosity and is difficult to melt. The present invention limits the range of SiO2 content to 50-60%.

[0018] In B2O3, boron exists as boron-oxygen triangles at high temperatures, which can reduce viscosity. However, when the boron content reaches a certain value, it increases the viscosity instead, so if the boron content is too high, it is disadvantageous to production. Also, if the B2O3 content is too high, the SiO2 lattice is easily precipitated and phase separation occurs. Also, the addition of B2O3 reduces the amount of B 3+ is introduced to form BO, whose bond energy is greater than the Si-O bond energy, and can play a role in stabilizing the glass network structure in the glass and limiting the polarization of oxygen ions. Therefore, the addition of B2O3 can reduce the dielectric constant and dielectric loss. The present invention limits the range of B2O3 content to 20-30%.

[0019] The addition of Al2O3 can effectively inhibit the crystallization of glass. In multi-component glass, Al2O3 can play a role in connecting the broken network, so that the network structure becomes tighter and the glass strength is improved, but the Al-O bond energy is weaker than the Si-O bond energy, so that the amount of free oxygen increases and the loss increases. The present invention limits the range of Al2O3 content to 8-18%.

[0020] CaO belongs to the network structure, and the calcium ion coordination number is generally 6. It has low activity in the structure, is generally difficult to precipitate from the glass, and has high activity at high temperatures. Ca2+ CaO polarizes bridge oxygen and weakens silicone bonds, which reduces viscosity, shortens material life and increases loss due to free oxygen. The present invention limits the CaO content to 1-6%.

[0021] In addition to SnO2 and F2, the present invention further adds MgO, which can reduce the viscosity of the glass system. However, if the content is too high, the dielectric constant and dielectric loss will increase, so the present invention limits the MgO content range to MgO<2.0.

[0022] P2O5 is a glass former that always exists as phosphorus oxygen tetrahedron in the glass structure. As the skeleton of glass, it can increase the phase separation temperature of glass, improve the temperature resistance of glass, and shorten the material properties of glass. In technical research, it was found that the softening point temperature of glass after P was introduced was higher than that before P was introduced, which contributes to improving the temperature resistance of the subsequent products. In addition, a single P2O5 raw material is prone to moisture absorption and is prone to agglomeration during the raw material blending process, which deteriorates the uniformity of the blended material and has high requirements for storage conditions. Therefore, the present invention introduces P2O5 into aluminum metaphosphate or condensed aluminum phosphate raw material to uniformly disperse P2O5 in the blended material, and the dissolution rate of B2O3 during the melting process of the blended material is fast and is locally wrapped in the uniformly distributed P2O5, reducing the amount of volatilization and reducing gas emissions. However, if the amount introduced is too large, the low-temperature viscosity will increase significantly, and if the P content is too high, it will be easy to take away free oxygen from B, causing devitrification of glass and crystallization. The present invention has discovered that when the Al2O3 content is greater than 8, it is effective in suppressing phase separation due to the introduction of high B and P, and by controlling the ratios of Al2O3, P2O5, and B2O3, the glass forming temperature can be lowered and crystal precipitation can be suppressed. In the present invention, the P2O5 content is controlled to the range of 0.05 to 5%.

[0023] Alkali metal oxides Li2O, K2O, and Na2O rapidly reduce the glass viscosity characteristics and contribute to the melting and clarification of glass. However, the bond between alkali metals and oxygen is very easy to polarize, and significantly increases the dielectric loss. The present invention adds a small amount of Li2O to reduce the viscosity under the premise of ensuring the dielectric loss, and contributes to glass melting. The present invention strictly controls the content of K2O and Na2O in the raw materials, and a small amount of K2O and Na2O is introduced from the impurities in the raw materials, so there is no need to add them. The present invention limits the range of Li2O to 0.05-0.5%, K2O+Na2O≦0.05%, to ensure that a glass with low dielectric loss can be obtained at a low melting and smelting temperature.

[0024] SnO2 decomposes at high temperature to generate O2, which reduces the gas partial pressure and is favorable for bubble discharge. More importantly, the SnO2+Li2O of the present invention functions as a composite fining agent, and Sn 4+ Due to interference from the outer electron layer, Li + The polarization effect of Li2O is strengthened, effectively enhancing the beneficial effects of Li2O, reducing the surface tension of the glass liquid during the glass fining process, efficiently discharging bubbles, improving glass uniformity, and achieving the zero bubble rate required for low dielectric glass fiber production. In addition, the melting temperature of the compounding materials is significantly reduced, reducing the volatilization of B and F. The present invention controls the range of SnO2 content to 0.05-0.5%, and the weight percentage ratio SnO / Li2O content to 0.2-3 weight%.

[0025] F has a small atomic radius and is less polarizable than O atoms. It forms Si-F bonds with Si, replaces a part of Si-O, and acts as a meshwork in the glass network. At the same time, the strength of the Si-F, BF, and Al-F bonds formed in the glass is weaker than the strength of the Si-O, BO, and Al-O bonds. This dual action reduces the melting temperature of the glass, reduces the viscosity, and reduces the surface tension of the glass, thereby contributing to reducing the difficulty of the glass forming process. In addition, the formed Si-F bonds are less polarizable, reducing the dielectric loss. The present invention controls the F2 content to a range of 0.2 to 1.5%.

[0026] In addition, the ratio of the contents of F2 and SnO2 in the present invention greatly affects the dielectric loss of glass, and when a small amount of SnO2 is introduced, the two work together to significantly reduce the dielectric loss. When the weight percentage ratio F2 / SnO2 is in the range of 1 to 5, the effect of the present invention is clear. Experimental results show that the object of the present invention cannot be achieved by adding F2 or SnO2 alone or when the range of F2 / SnO2 is not 1 to 5. When F2 and SnO2 are used in combination, F2 disperses around SnO2 to form Sn-F bonds, and works with Si-F, BF, and Al-F to further reduce the melting temperature of glass, reduce the viscosity, and reduce the surface tension of glass.

[0027] From the above, in the present invention, by adding SnO2 and F2 simultaneously and controlling the F2 / SnO2 ratio, not only can the glass fiber have a low dielectric constant and dielectric loss, but also the viscosity of the glass fiber can be reduced, and the number of bubbles in the glass fiber can be reduced to zero.

[0028] In addition, in the present invention, by adding P2O5 in addition to SnO2 and F2 and controlling the ratio of P2O5 / (F2+SnO2) to within the range of 2-5, the dielectric constant and dielectric loss of the glass fiber can be further reduced.

[0029] In the present invention, due to the interaction between the components, the resulting glass fiber composition has a low dielectric constant, low dielectric loss, few bubbles, and low viscosity, and is excellent in glass performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The present invention will now be further described with reference to embodiments.

[0031] Examples 1 to 7 The compositions of the glass fiber compositions having low dielectric loss in Examples 1 to 7 are shown in Table 1.

[0032] (1) Each compound was mixed in a certain ratio according to the content of each component, and after uniform mixing, the mixture was placed in a platinum crucible and melted at 1550 to 1600°C, and drawn at less than 1350°C to produce glass fiber. To ensure that the glass has sufficient strength and is suitable for the wire drawing process, elastic modulus strength measurement is performed: The glass is cut into a glass block of 20*20*15mm (length*width*thickness), and the test surface is smooth and flat. The thickness of the glass is measured using an ultrasonic thickness gauge according to the following formula: [The actual sound velocity unit measured by the thickness gauge is mm / us, so the sound velocity value (cm / s) in the formula below is the actual measured value x 10 5 and density unit: g / cm 3 Then, simply substitute the necessary data into the calculation.

[0033]

number

[0034]

number

[0035] (2) To measure the dielectric properties, the homogeneously mixed materials are placed in a platinum crucible and melted. The molten sample is then annealed at 600°C to remove stress, after which it is cut into a Φ50*2mm sample and tested at 10GHz using a network vector analyzer. Table 1 shows the data obtained by measuring the indices of the glass fiber composition, i.e., the lg3.0 temperature, the liquidus temperature, ΔT, the dielectric constant, the dielectric loss, the elastic modulus, and the number of bubbles.

[0036] Comparative Examples 1 to 6 The compositions of the glass fiber compositions in Comparative Examples 1 to 6 are shown in Table 2. Table 2 shows the data of the measurement of the indexes of the glass fiber composition, i.e., the lg3.0 temperature, the liquidus temperature, ΔT, the dielectric constant, the dielectric loss, the elastic modulus, and the number of bubbles.

[0037] [Table 1]

[0038] [Table 2]

[0039] In the table, lg3.0 is the temperature when the glass liquid viscosity is 1000 poise, and is the glass forming temperature, i.e., the wire drawing temperature. The upper limit of the liquidus temperature, i.e., the crystallization temperature or phase separation temperature, is the upper limit of the devitrification temperature of the glass. The greater the difference between the forming temperature and the liquidus temperature, the more advantageous it is for wire drawing.

[0040] Analyzing the data in Tables 1-2, the ratio of SnO2 / Li2O in Comparative Example 1 is 5.00, which is outside the range of 0.2-3. The ratio of F2 / SnO2 in Comparative Example 3 is 6.00, which is outside the range of 1-5. The ratio of P2O5 / (F2+SnO2) in Comparative Example 4 is 1.58, which is outside the range of 2-5. The viscosity of the glass fiber increases, and the number of bubbles in the glass fiber also increases to different degrees.

[0041] Comparing Example 1 with Comparative Examples 2, 5, and 6, it can be seen that, compared to Example 1 of the present invention, Comparative Example 2 does not add SnO2, Comparative Example 5 does not add F2, and Comparative Example 6 does not add SnO2 and F2, which leads to an increase in the viscosity of the glass fiber and an increase in the number of bubbles in the glass fiber. In the present invention, by adding SnO2 and F2 simultaneously and controlling the ratio of F2 / SnO2, not only does the glass fiber have a low dielectric constant and dielectric loss, but also the viscosity of the glass fiber is reduced and the number of bubbles in the glass fiber becomes zero. In addition, in the present invention, by adding P2O5 and controlling the ratio of P2O5 / (F2+SnO2) to a range of 2 to 5, the dielectric constant and dielectric loss of the glass fiber are further reduced.

Claims

1. It consists of the following components by mass percentage, and the content of each component is: Yes 2 :5~60%、 B 2 O 3 :20~30%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :8~188%、 CaO: 1 to 6%, F 2 :0.2~1.50%、 SnO 2 :0.05~0.5%、 Li 2 O:0.05~0.5%、 K 2 O+Na 2 O≦0.05%; SnO 2 and Li 2 The mass percentage content of O is SnO 2 / Li 2 The range of O is 0.2 to 3; F 2 and SnO 2 The mass percentage content of F 2 / SnO 2 A glass fiber composition having low dielectric loss, characterized in that the range of

2. The content of each component in mass percentage is: Yes 2 :5~60%、 B 2 O 3 :20~30%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :8~188%、 CaO: 1 to 6%, F 2 :0.2~1.50%、 P 2 O 5 :0.05~5%、 SnO 2 :0.05~0.5%、 Li 2 O:0.05~0.5%、 K 2 O+Na 2 O≦0.05%; SnO 2 and Li 2 The mass percentage content of O is SnO 2 / Li 2 The range of O is 0.2 to 3; F 2 and SnO 2 The mass percentage content of F 2 / SnO 2 is in the range of 1 to 5, P 2 O 5 , F 2 and SnO 2 The mass percentage content of P 2 O 5 / (F 2 + SnO 2 ) is in the range of 2 to 5.

3. The content of each component in mass percentage is: Yes 2 :5~60%、 B 2 O 3 :20~30%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :8~188%、 CaO: 1 to 6%, F 2 :0.2~1.50%、 SnO 2 :0.05~0.5%、 Li 2 O:0.05~0.5%、 K 2 O+1 2 O≦0.05%、 0%<MgO<2.0%, SnO 2 and Li 2 The mass percentage content of O is SnO 2 / Li 2 The range of O is 0.2 to 3; F 2 and SnO 2 The mass percentage content of F 2 / SnO 2 A glass fiber composition having low dielectric loss, characterized in that the range of

4. The content of each component in mass percentage is: Yes 2 :5~60%、 B 2 O 3 :20~30%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :8~188%、 CaO: 1 to 6%, F 2 :0.2~1.50%、 P 2 O 5 :0.05~5%、 SnO 2 :0.05~0.5%、 Li 2 O:0.05~0.5%、 K 2 O+1 2 O≦0.05%、 0%<MgO<2.0%, SnO 2 and Li 2 The mass percentage content of O is SnO 2 / Li 2 The range of O is 0.2 to 3; F 2 and SnO 2 The mass percentage content of F 2 / SnO 2 The range of is 1 to 5. P 2 O 5 , F 2 and SnO 2 The mass percentage content of P 2 O 5 / (F 2 + SnO 2 ) is in the range of 2 to 5.

Citation Information

Patent Citations

  • JPP7131733B

  • Low Dielectric Glass And Fiber Glass

    US20140235424A1

  • Use of MgO, AnO, and Rare Earth Oxides for Making Improved Low Dielectric Fibers with Improved Low Thermal Expansion Coefficient for High Boron Aluminosilicate Compositions

    US20200039870A1

  • Glass composition and glass fiber and method for producing same

    WO2022168963A1